Oxford Scholarship Online 2018
DOI: 10.1093/oso/9780198812579.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Class, Politics, and the Decline of Deference in England, 1968-2000

Abstract: This book examines class identities and politics in late twentieth-century England. Class remained important to ‘ordinary’ people’s identities and their narratives about social change in this period, but in changing ways. Using self-narratives drawn from a wide range of sources, the book shows that many people felt that once-clear class boundaries had blurred since 1945. By the end of the period, ‘working-class’ was often seen as a historical identity, related to background and heritage. The middle classes bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(14 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…In the post-war boom, a time of unprecedented reduction in economic inequality, social policy discourse relating to poverty emphasized its structural determinants and resisted ‘judgementalism’ and ‘the politics of character’ that Frank Field later defended (Welshman, 2006: xxvi). Establishment models of character may have lost influence in popular culture in the 1960s and 1970s with the ‘the decline of deference’ (Sutcliffe-Braithwaite, 2018), and the lampooning of the upper class in satire and comedy such as Beyond the Fringe and Monty Python . Yet antagonism towards the poor did not disappear, and towards the end of the 1970s, in both popular culture and politics, the pendulum began to swing back the other way, and blaming the poor for their poverty began to re-emerge (Deacon, 1987, 1996).…”
Section: Political (Mis-)usesmentioning
confidence: 99%
“…In the post-war boom, a time of unprecedented reduction in economic inequality, social policy discourse relating to poverty emphasized its structural determinants and resisted ‘judgementalism’ and ‘the politics of character’ that Frank Field later defended (Welshman, 2006: xxvi). Establishment models of character may have lost influence in popular culture in the 1960s and 1970s with the ‘the decline of deference’ (Sutcliffe-Braithwaite, 2018), and the lampooning of the upper class in satire and comedy such as Beyond the Fringe and Monty Python . Yet antagonism towards the poor did not disappear, and towards the end of the 1970s, in both popular culture and politics, the pendulum began to swing back the other way, and blaming the poor for their poverty began to re-emerge (Deacon, 1987, 1996).…”
Section: Political (Mis-)usesmentioning
confidence: 99%
“…MO restarted in 1981 and has continued ever since to issue 'directives' containing open-ended sets of questions to a panel of c. 1000 volunteer writers every three or four months. Numerous historians and social scientists have demonstrated that MO materials can be used as evidence of popular understandings of various aspects of everyday life including race (Kushner, 2004), social class (Savage, 2010;Sutcliffe-Braithwaite, 2017), and formal politics (Clarke et al, 2018).…”
Section: Using Mass Observation To Identify Emotional Regimesmentioning
confidence: 99%
“…As historian Florence Sutcliffe-Braithwaite has noted, the 1980s into the 1990s marked a period of widening income inequality in Britain, but simultaneously a decline in the currency of class as an appropriate analytical discourse. 89 While Sutcliffe-Braithwaite suggests that 'the late 1970s and early 1980s did see something of a spike in cultural interest in "class"', this interest was arguably that of the eulogist, as sociologist Gordon Marshall, amongst others, noted in 1988: obituaries . .…”
Section: 'What Was True In Whitehall Was True In Britain As a Whole'mentioning
confidence: 99%